A self-consistent determination of the RVB and SC gaps in the YRZ ansatz. (12th January 2017) - Rao, Zi-Ye; Wang, Xiao-Min; Jiang, Hong-Min
Abstract: A correct understanding of the origin of the pseudogap in high temperature (high- T c ) cuprate superconductors is considered to be a peripheral breakthrough in the understanding of the microscopic mechanism of the high- T c superconductivity. Yang–Rice–Zhang (YRZ) ansatz is an important phenomenological theory to describe the phenomenon of pseudogap. However, in the framework of YRZ, the pseudogap (resonant valence bond (RVB) gap) and the superconducting (SC) gap are unable to have a self-consistent determination at different doping concentrations, and this severely limits the application of the YRZ ansatz. Based on the YRZ ansatz, this study develops a technical method to determine the RVB and SC gaps in a self-consistent manner. It is revealed that the self-consistent calculations of the doping dependence of RVB, SC gaps and spectral function are not only consistent with the empirical gap formula in the YRZ framework, but also consistent with the doping evolution of the Fermi surface observed in the angle-resolved photoemission spectroscopy (ARPES) experiments. Our method will greatly extend the applications of the YRZ ansatz, and will deepen our understanding of the origin of pseudogap as well as the mechanism of high- T c superconductivity.